Modeling of binary nanooxides with solid solutions and mixed phases - V. M. Gun’ko (Хімія, фізика та технологія поверхні)
The electronic structure of individual metal (Ti, Al) or metalloid (Si) oxides as well as complex (binary, ternary, etc.) oxides is of importance from a practical point of view. In various applications of these materials as catalysts, sorbents, carriers, fillers, etc., the bandgap, polarizability, conductivity, and dielectric characteristics play a crucial role in the application efficiency. Therefore, accurate determination of these characteristics is strongly required. Sometimes theoretical determination of the characteristics is simpler, especially for large series of complex materials with varied compositions, by using quantum chemical methods (i.e., computations without synthesis) than experimental ones (synthesis and measurements). Upon computations with quantum chemical methods, selection of a method adequate to a task is important to obtain more accurate information. Therefore, in this study, two semiempirical methods (PM7 and DFTB+ used in semiempirical packages (MOPAC, DFTB+) and implemented in the most known packages such as Gaussian, GAMESS, AMS, etc.) have been used in parallel to DFT (mainly ?B97X-D/cc-pVDZ) to compute various clusters (22, 35, 88, 94, and 111 units) with silica, alumina, titania, titania/silica, and alumina/silica. The computations show that the bandgap value (Eg) of titania is mostly accurately computed with DFTB+ using cluster and periodic boundary conditions approaches. However, for other systems, the DFTB+ Eg values are typically underestimated. The PM7 and DFT bandgap values are more appropriate with the use of the potential approach V–1 (computation of the virtual levels of the systems with removed one electron) giving Eg1. Detailed analysis of the integral density of electron states and density of atomic charges summarized by atom types reveals several reasons of nonmonotonic changes in the Eg values vs. composition of binary oxides. As a whole, the PM7 and DFT methods give correct tendencies in the changes in the Eg and Eg1 values vs. binary oxide compositions, but the Eg values are typically overestimated in contrast to underestimated values by DFTB+. Water adsorbed in a low amount on oxide clusters provides a significant stabilization of a surface since the Gibbs free surface energy strongly decreases especially for titania-containing systems. This explains more effective adsorption of water from air onto nonporous binary oxides or titania in comparison to silica.